2021
DOI: 10.1016/j.ejpn.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute encephalitis in pediatric multisystem inflammatory syndrome associated with COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 4 publications
(7 reference statements)
5
33
2
1
Order By: Relevance
“…In the present case, SARS-CoV-2 PCR and nucleocapsid antibodies were negative, highlighting lack of SARS-CoV-2 exposure. Our patient with encephalopathy and focal neurological signs on admission, focal EEG slowing and normal CSF analysis is similar to recently reported cases of acute encephalitis in the setting of MIS-C [30].…”
Section: Discussionsupporting
confidence: 89%
“…In the present case, SARS-CoV-2 PCR and nucleocapsid antibodies were negative, highlighting lack of SARS-CoV-2 exposure. Our patient with encephalopathy and focal neurological signs on admission, focal EEG slowing and normal CSF analysis is similar to recently reported cases of acute encephalitis in the setting of MIS-C [30].…”
Section: Discussionsupporting
confidence: 89%
“…The number of children hospitalised for COVID‐19 in just January 2022 appeared to be disproportionally higher than in 2020 and 2021 and one‐third had epileptic seizures. This was much higher than previously reported 3–5 and appears to be related to the Omicron variant.…”
Section: Figurecontrasting
confidence: 67%
“…Although the possibility of SARS-CoV-2 infecting the central nervous system directly is still disputed, owing to the very low level of angiotensin-converting enzyme 2 (ACE-2) expression in the brain, human brain gene expression and immunohistochemistry have revealed that SARS-CoV-2 could infiltrate into the hypothalamus [ 18 ]. Interestingly, neuroimaging in children with neurologic manifestations has demonstrated only a low prevalence of acute encephalitis in MIS-C associated with Covid-19 [ 19 , 20 ]. Our patient had a normal brain CT scan, and a total recovery from his coma without any neurologic sequela, suggesting his mental status changes were from DKA.…”
Section: Discussionmentioning
confidence: 99%